1997
DOI: 10.1109/78.622943
|View full text |Cite
|
Sign up to set email alerts
|

Perfect reconstruction versus MMSE filter banks in source coding

Abstract: Abstract-Classically, the filter banks (FB's) used in source coding schemes have been chosen to possess the perfect reconstruction (PR) property or to be maximally selective quadrature mirror filters (QMF's). This paper puts this choice back into question and solves the problem of minimizing the reconstruction distortion, which, in the most general case, is the sum of two terms: a first one due to the non-PR property of the FB and the other being due to signal quantization in the subbands. The resulting filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Restricting ourselves to the class of biorthogonal FB when quantizers are present is therefore a loss of generality. A similar observation was given by Gosse and Duhamel [4] calling this more general class of filter banks minimum meansquare-error (MMSE) filter banks. Kovacevic [2] also reaches the same conclusion for the case where the subband quantizer is modeled as a Lloyd-Max quantizer.…”
mentioning
confidence: 69%
“…Restricting ourselves to the class of biorthogonal FB when quantizers are present is therefore a loss of generality. A similar observation was given by Gosse and Duhamel [4] calling this more general class of filter banks minimum meansquare-error (MMSE) filter banks. Kovacevic [2] also reaches the same conclusion for the case where the subband quantizer is modeled as a Lloyd-Max quantizer.…”
mentioning
confidence: 69%
“…Recent research has shown that reconstruction distortion can be minimized in the mean square sense (MMSE) by relaxing PR constraints and tuning the synthesis filters [154,155,156,157,158,159,160]. Naturally, mean square error minimization is of limited value for subband audio coders.…”
Section: ) Dwpt Coder With Perceptually Optimized Synthesis Waveletsmentioning
confidence: 99%
“…The same idea appears in [7] with FIR filters, and is extended to the 2-D case. Further generalization is shown in [1], where general solutions are given for jointly optimizing parallel, critically sampled, synthesis filters and uniform subband quantizers. In comparison, [3] is mainly an asymptotic study of matrix Wiener filters with infinite length.…”
Section: A Connection With Previous Workmentioning
confidence: 99%
“…Section II briefly recalls the problem of optimizing a coding scheme based on parallel, critically sampled analysis filter banks with subbands of equal widths and uniform quantization [1]. In Section III, this optimization problem is modified so as to constrain the synthesis filters to be modulated versions of a low-pass prototype.…”
Section: B Outline Of the Papermentioning
confidence: 99%
See 1 more Smart Citation